Understanding networks of actors involved in refugee access to higher education in Canada, England and France: A digital comparative approach. Issue 3 (1st December 2021) - Viczko, Melody; Détourbe, Marie-Agnès; McKechnie, Shannon
Abstract: In times of intense migrations, securing a brighter future through education has become a growing concern in many societies. In particular, access to higher education for refugees has been the object of multiple initiatives among governments, civil society and non-government organisations. However, only 3 per cent of refugees access higher education, and there is a need to better understand, support and develop successful access for refugees among policymakers, educators and researchers. This research takes an original comparative digital approach to identifying those networks in three countries: Canada, England and France. Our findings suggest that the nature of issues for refugee access to higher education is constructed differently in each national context, as the social relations between government, civil society, non-government agencies and higher education institutions are uniquely configured.